2016
DOI: 10.5116/ijme.576f.d074
|View full text |Cite
|
Sign up to set email alerts
|

Learning strategies, study habits and social networking activity of undergraduate medical students

Abstract: ObjectivesTo determine learning strategies, study habits, and online social networking use of undergraduates at an Irish medical school, and their relationship with academic performance. MethodsA cross-sectional study was conducted in Year 2 and final year undergraduate-entry and graduate-entry students at an Irish medical school. Data about participants’ demographics and educational background, study habits (including time management), and use of online media was collected using a self-report questionnaire. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 32 publications
1
63
1
2
Order By: Relevance
“…Considering learning has a rich and various heritages, there are many learning theories that a number of them emphasize the importance of learning strategies including: double loop learning (Argyris), conversation theory (Pask), and lateral thinking (DeBono). Weinstein (1991) discusses learning strategies in the context of social interaction, an important aspect of Situated Learning Theory (2).Learning strategies refer to methods that students use to learn. This ranges from techniques for improved memory to better studying or test-taking strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Considering learning has a rich and various heritages, there are many learning theories that a number of them emphasize the importance of learning strategies including: double loop learning (Argyris), conversation theory (Pask), and lateral thinking (DeBono). Weinstein (1991) discusses learning strategies in the context of social interaction, an important aspect of Situated Learning Theory (2).Learning strategies refer to methods that students use to learn. This ranges from techniques for improved memory to better studying or test-taking strategies.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown that interleaving is better than other techniques in helping people retain knowledge in the long term 46151617…”
Section: Mixing Things Upmentioning
confidence: 99%
“…Many students begin by using the same techniques that worked for them at school, such as revisiting material and making notes. Research has shown, however, that these techniques alone have a limited impact on long term knowledge retention and academic success 1234…”
mentioning
confidence: 99%
“…It includes long hours of study, little sleep, much content absorbed passively, surface learning and a tendency towards greater study loads on days preceding tests. 13,14,16 Nevertheless, our findings attempt not only to describe the study routine, but also to try to understand how surface or deeper learning might influence students. It was found that students with a surface approach had poorer quality of sleep and more frequently chose to study just before the exam; they used materials and summaries originating from classes, cheated more frequently and exhibited greater preference for multiple-choice questions.…”
Section: Discussionmentioning
confidence: 99%